CD101 surface expression discriminates potency among murine FoxP3+ regulatory T cells. - Fernandez, I; Zeiser, R; Karsunky, H; Kambham, N; Beilhack, A; Soderstrom, K; Negrin, R; Engleman, E (2007)
CD4+CD25+FoxP3+ regulatory T cells (Treg) have been shown to be protective in animal models of autoimmunity and acute graft-vs-host disease. However, owing to the functional heterogeneity among CD4+CD25+ T cells, surface markers expressed selectively on functionally active Treg would be useful for purposes of identifying and isolating such cells. We generated a rabbit mAb against murine CD101, a transmembrane glycoprotein involved in T cell activation. Among freshly isolated T cells, CD101 was detected on 25-30% of CD4+CD25+ Treg and approximately 20% of conventional memory T cells. CD101(high) Treg displayed greater in vitro suppression of alloantigen-driven T cell proliferation as compared with CD101(low) Treg. In a model of graft-vs-host disease induced by allogeneic bone marrow transplantation in vivo bioluminescence imaging demonstrated reduced expansion of donor-derived luciferase-labeled conventional T cells in mice treated with CD101(high) Treg, compared with CD101(low) Treg. Moreover, treatment with CD101(high) Treg resulted in improved survival, reduced proinflammatory cytokine levels and reduced end organ damage. Among the CD101(high) Treg all of the in vivo suppressor activity was contained within the CD62L(high) subpopulation. We conclude that CD101 expression distinguishes murine Treg with potent suppressor activity.